1993
DOI: 10.1148/radiology.186.2.8421736
|View full text |Cite
|
Sign up to set email alerts
|

Complete obstruction of the nasolacrimal system. Part I. Treatment with balloon dilation.

Abstract: Fluoroscopically guided balloon dilation in treatment of complete obstruction of the nasolacrimal system was assessed in 39 eyes of 35 patients. All patients had severe epiphora. With nasal endoscopic guidance, a 0.018-inch guide wire was introduced through the superior punctum into the inferior meatus of the nasal cavity and was pulled out through the nasal aperture with a hemostat. A deflated angioplasty balloon catheter was passed retrograde over the guide wire through the inferior meatus until it straddled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 0 publications
3
27
0
3
Order By: Relevance
“…Transluminal balloon dilation of the LDS has been proposed as an alternative to surgical treatment. 3,4 Placement of nasolacrimal polyurethane stents in the LDS is another less invasive approach to the treatment of epiphora. 5 The cause of epiphora can be diagnosed by physical examination, diagnostic clinical tests, and imaging procedures.…”
mentioning
confidence: 99%
“…Transluminal balloon dilation of the LDS has been proposed as an alternative to surgical treatment. 3,4 Placement of nasolacrimal polyurethane stents in the LDS is another less invasive approach to the treatment of epiphora. 5 The cause of epiphora can be diagnosed by physical examination, diagnostic clinical tests, and imaging procedures.…”
mentioning
confidence: 99%
“…A lack of steerability and stiffness could be ob served when small angiographic guide wires with soft, flop py tips were used for manipulation in the lacrimal drainage system. Song et al [8] initially used the stiff end of the guide wire to improve the passage through curves and tough obstructions. The sharp end of the wire may cause traumatic lesions.…”
Section: O N C Lu S Io N S and Discussionmentioning
confidence: 99%
“…Residual stenoses remained probably because dilation is limited by a narrow bone canal and scarry stric tures of the wall. Song et al [7,8] reported a high rate of 45% recurrent obstructions after recanalization of com pletely occluded tear ducts by means of balloon dilation. In our group of patients also tendencies towards rcobstruction are visible.…”
Section: O N C Lu S Io N S and Discussionmentioning
confidence: 99%
“…In adults, success rates have ranged from 10 to 75%. [46][47][48] success rate of endoscopically assisted balloon dacryocystoplasty and silicone intubation with silicone intubation alone in adults with incomplete NLDO. 48 There was no statistically significant difference between the two groups (53.8% in the silicone intubation group and 60.8% in the balloon dacryocystoplasty group).…”
Section: Balloon Dacryocystoplastymentioning
confidence: 99%